ISLAMIC GROUP LENDING MODEL (GLM) AND FINANCIAL INCLUSION - Abrista Devi; Aam Rusydiana (UNISSULA, 2016)
The lack of capital access from poor society to Indonesia banking is greater. These all are caused by poor society don’t have enough collateral which is requested by bank officer to get loan. Non-bank financial institution is one of micro-financial institution which has covered all of poor society and also maximizing the existency of UMKM, include social model credit capital (GLM). The aim of this study to see the form of Group Lending Model (GLM) and its’ impact to their members social structure. This research also tries to give the solutions such as the first GLM development strategy in other to be more effective and efficient. The methods used are Structural Equation Modeling (SEM) and Interpretaive Structural Modeling (ISM). Based on the measurement of some indicators there are the participation indext of society, society development, good repayment rate, good cross reporting, and penalty implications appropriate with the regulations. The results show that GLM programme, the society feel the differenciation from the economic and social condition between before and after following this programme. This is valuable invention for economic studies. GLM development strategy are devided into 7 levels with its important elements are : the needy of similiarity fund access for all of financial institution. The needy of human resource quality development as the pioneer of group lending model, and the importance of inclusive financial to all financial system.